Follicular Becker's nevus: A new clinical variant - Yashpal Manchanda; Binod K Khaitan; M Ramam; Sudip Das; Nawaf Al-Mutairi (Wolters Kluwer Medknow Publications, 2020)
Becker's nevus, also known as pigmented hairy epidermal nevus, is characteristically described as a unilateral, hairy, light to dark brown macule with sharply outlined but irregular border. The etiopathogenesis of Becker's nevus is still not clearly understood. Perifollicular pigmentation has been described earlier by some authors. But, Becker's nevus presenting exclusively with follicular lesions has not been described. We are reporting a series of patients of Becker's nevus with follicular lesions. The diagnosis in all the patients was made after clinicopathological correlation. Follicular epithelium may hold a significant role in the etiopathogenesis of Becker's nevus.